Postnatal development of eustachian tube cartilage. A study of normal and cleft palate cases - Takasaki, Kenji; Sando, Isamu; Balaban, Carey D; Ishijima, Ken (International journal of pediatric otorhinolaryngology, 2000)
Infants with cleft palate (CP) display eustachian tube (ET) dysfunction. This study compared the postnatal development of the volume of ET cartilage in 34 normal cases and 10 CP cases using a personal computer. In cases with age under 1 month old, the total volume of ET cartilage was 61.94±20.89 mm 3 (mean±S.D.) in 16 normal control cases and 50.07±24.69 mm 3 in nine CP cases ( t-test, not significantly different from normal). The ratio of lateral lamina (LL) to medial lamina (ML) volume (LL/ML) was reduced significantly ( t-test, P<0.001) from 0.23±0.07 in 16 normal control cases to 0.09±0.05 in nine CP cases under 1 month old. In 34 normal ET cases whose ages were under 20 years, statistically significant positive correlations were found between the total volume of ET cartilage ( y1) and age ( x), volume of LL ( y2) and age, and volume of ML ( y3) and age ( P<0.01, r=0.731, 0.614, 0.719). The regression lines were y1=20.37 x+95.57, y2=2.02 x+15.60, and y3=18.35 x+79.97. With the result obtained from this study, it is assumed that immaturity of the ET cartilage in infants, especially that of LL of the ET cartilage in CP infants, may be a significant risk factor for developing otitis media with effusion.